Comparison of Hemodynamic Responses in Hypertensive Patients Undergoing Endotracheal Intubation Using Direct Laryngoscope and Video Laryngoscope at Arifin Achmad Regional Hospital, Riau Province - Marthendro, Triade; Irawan, Dino; Harahap, Sari; Muharrami, Vera (South Eastern European Journal of Public Health, 2024)
This study investigates the hemodynamic responses in hypertensive patients undergoing endotracheal intubation using either a direct or video laryngoscope at Arifin Achmad Regional Hospital, Riau Province. The purpose is to compare blood pressure, mean arterial pressure, and heart rate variations across both methods to identify which procedure offers better hemodynamic stability. Employing an experimental analytic method with a cross-sectional approach, data were collected from patients who met the inclusion criteria and were randomly assigned to either the direct or video laryngoscope group. Results indicate that patients intubated with the video laryngoscope exhibited significantly lower increases in blood pressure and mean arterial pressure during both preintubation and postintubation phases compared to those using the direct laryngoscope. These findings highlight the video laryngoscope’s effectiveness in minimizing hemodynamic stress in hypertensive patients. Conclusively, the video laryngoscope is recommended for better hemodynamic management during intubation in hypertensive patients.